Multimodal bioimaging using nanodiamond and gold hybrid nanoparticles - Lin, Yu-Chung; Perevedentseva, Elena; Lin, Zhe-Rui; Chang, Chia-Chi; Chen, Hsiang-Hsin; Yang, Shun-Min; Lin, Ming-Der; Karmenyan, Artashes; Speranza, Giorgio; Minati, Luca; Nebel, Christoph; Cheng, Chia-Liang (Scientific reports, 2022)
Hybrid core–shell nanodiamond-gold nanoparticles were synthesized and characterized as a novel multifunctional material with tunable and tailored properties for multifunctional biomedical applications. The combination of nanostructured gold and nanodiamond properties afford new options for optical labeling, imaging, sensing, and drug delivery, as well as targeted treatment. ND@Au core–shell nanoparticles composed of nanodiamond (ND) core doped with Si vacancies (SiV) and Au shell were synthesized and characterized in terms of their biomedical applications. Several bioimaging modalities based on the combination of optical and spectroscopic properties of the hybrid nano-systems are demonstrated in cellular and developing zebrafish larvae models. The ND@Au nanoparticles exhibit isolated ND’s Raman signal of sp 3 bonded carbon, one-photon fluorescence of SiV with strong zero-phonon line at 740 nm, two-photon excited fluorescence of nanogold with short fluorescence lifetime and strong absorption of X-ray irradiation render them possible imaging agent for Raman mapping, Fluorescence imaging, two-photon Fluorescence Lifetime Imaging (TP-FLIM) and high-resolution hard-X-ray microscopy in biosystems. Potential combination of the imaging facilities with other theranostic functionalities is discussed.